Seismic performance evaluation and experimental validation of steel-fiber-reinforced high-strength-concrete composite shear walls. (January 2022) - Zhang, Ying; Zhang, Hongmei; Lu, Xilin
Abstract: The seismic performance evaluation method for the Steel-fiber-reinforced High-strength-concrete (SFRHSC) composite shear walls are studied in this paper. Currently, seismic design codes do not include such high-performance elements, due to the lack of reliable predictive equations for the lateral load bearing capacity and the deformation capacity, which are essential quantities in design. In this study, the capacity predictive equations for the wall element are proposed, corresponding to four different performance levels with "flexure-dominated failure" mode. Cross-sectional analysis on stress and strain with a series of parameters determined according to experimental results is used to attain the predictive equations. The constitutive models for unconfined and confined SFRHSC considering fiber-bridging action are developed and discussed. Additionally, the flexural and shear displacements are quantified separately to allow the estimation of the total deformation. The accuracy of such equations is validated against experimental results, from which it is ascertained that the proposed models are able to accurately predict both the material and the element behavior. The results of this study are relevant for the development of the next generation of seismic design codes.